Manual lymphatic drainage in the treatment of chronic venous disease - Crisóstomo, Rute (2017)
Chronic venous disease (CVD) is a chronic condition that is associated with venous hypertension, vein’s valves damage, venous obstruction, and calf muscle pump impairment. This blood circulatory condition is also characterized by important inflammatory changes affecting the skin, the subcutaneous tissue and the muscles, which are probably triggered by blood stasis and venous edema. With disease progression, severe ulcerative skin damage might occur, which when present represent the more severe stage of this condition. CVD has a significant economic, social and health impact, mostly due to raised morbidity and chronicity. The treatment of patients with CVD might focus on both the symptoms and secondary changes of the disease, such as edema, skin and subcutaneous changes or ulcers. Usually, initial treatment of CVD patients involves a non-invasive, conservative treatment to reduce symptoms, treat secondary changes, and help prevent the development of secondary complications and the progression of the disease. Complementary, some interventional or surgical treatments can be undertaken. There are several conservative treatments to treat and prevent complications associated with CVD that have been described in the literature, like manual lymphatic drainage (MLD) and compression, physical exercise, intermittent pneumatic pressure, kinesio taping, electrical muscle stimulation, transcutaneous electrical nerve stimulation, hydrotherapy, and health education. Most of these techniques are complementary to compression therapy or pharmacological treatment. This chapter will address the role of physical therapists in the management of CVD. The chapter will begin by reviewing the basic physiopathology of CVD, including the role of calf muscle pump. The CEAP classification system and the chronic venous severity score will be presented, as these are main tools for clinical assessment of CVD severity. In the remainder of the chapter will address the physiological effects and recommendations for treating CVD of MLD, based on our clinical experience and own research.